The effectiveness of acupressure in the management of depressive symptoms and in improving quality of life in older people living in the community: a randomised sham-controlled trial. (2nd June 2020) - Molassiotis, Alex; Suen, Lorna; Lai, Claudia; Chan, Ben; Wat, Karen Hong Yun; Tang, Jenny; To, Kui-lung; Leung, Cheung-on; Lee, Sara; Lee, Paul; Chien, Wai Tong
Abstract: Objective: The primary aim of the current trial was to assess the clinical effectiveness of acupressure in the management of depression in elderly people compared to patients receiving sham acupressure or standard care alone. Methods: Randomized sham-controlled trial of acupressure, sham acupressure and standard care alone in older patients with depression living in the community. Patients with a score>/=8 in the Geriatric Depression Scale were recruited for this study. Intervention/sham treatments were provided four times/week for three months. Assessments related to depressive symptoms (primary outcome), well-being, resilience, spirituality and quality of life domains were carried out at baseline, end of the intervention and three-months after the intervention. Results: 118 patients were randomized to intervention (n = 40), sham (n = 40) or control arm (n = 38), with 84 patients providing final analysis data. Significant reduction in mean score of depressive symptoms was found in the acupressure group (from 10.6 (sd = 0.03) to 7.7 (sd = 0.07), p < 0.001 at end of intervention and 8.7 (sd = 0.8), p = 0.002 at follow-up) and the sham acupressure group (from 10.5 (sd = 0.3) to 8.4 (sd = 0.8), p = 0.005) at end of intervention and 8.4 (sd = 0.8), p = 0.006 at follow-up but not in the control group (from 10.8 to 9.9, p = 0.20). Resilience (p = 0.02) and spirituality (p = 0.02) were also improved in the intervention group at the end of intervention assessment but this change was not sustained at follow-up. Mind-body-spirit well-being and social functioning were improved both at the end of intervention and follow-up in the experimental as well as sham group. The sham group showed additional improvements in daily functioning and environmental quality of life. Conclusions: Although acupressure improved outcomes, a placebo effect was evident. Acupressure may be an effective approach to manage depression in elderly patients, but more evidence is needed in the future before it can be recommended for practice as well as more clear elucidation of any placebo effects.